Human β‐defensin‐1: A natural antimicrobial peptide present in amniotic fluid that is increased in spontaneous preterm labor with intra‐amniotic infection. (12th August 2018) - Varrey, Aneesha; Romero, Roberto; Panaitescu, Bogdan; Miller, Derek; Chaiworapongsa, Tinnakorn; Patwardhan, Manasi; Faro, Jonathan; Pacora, Percy; Hassan, Sonia S.; Hsu, Chaur‐Dong; Gomez‐Lopez, Nardhy
Abstract: Problem: Human β‐defensins (HBDs) are antimicrobial peptides that participate in the soluble innate immune mechanisms against infection. Herein, we determined whether HBD‐1 was present in amniotic fluid during normal pregnancy and whether its concentrations change with intra‐amniotic inflammation and/or infection. Method of Study: Amniotic fluid was collected from 219 women in the following groups: (a) midtrimester who delivered at term (n = 35); (b) term with (n = 33) or without (n = 17) labor; (c) preterm labor with intact membranes who delivered at term (n = 29) or who delivered preterm with (n = 19) and without (n = 29) intra‐amniotic inflammation and infection or with intra‐amniotic inflammation but without infection (n = 21); and (d) preterm prelabor rupture of membranes (pPROM) with (n = 19) and without (n = 17) intra‐amniotic inflammation/infection. Amniotic fluid HBD‐1 concentrations were determined using a sensitive and specific ELISA kit. Results: (a) HBD‐1 was detectable in all amniotic fluid samples; (b) amniotic fluid concentrations of HBD‐1 were changed with gestational age (midtrimester vs term no labor), being higher in midtrimester; (c) amniotic fluid concentrations of HBD‐1 were similar between women with and without spontaneous labor at term; (d) among patients with spontaneous preterm labor, amniotic fluid concentrations of HBD‐1 in women with intra‐amniotic inflammation/infection and in those with intra‐amniotic inflammation without infection were greater than in women without intra‐amniotic inflammation or infection who delivered preterm or at term; and (e) the presence of intra‐amniotic inflammation and infection in patients with pPROM did not change amniotic fluid concentrations of HBD‐1. Conclusion: HBD‐1 is a physiological constituent of amniotic fluid that is increased in midtrimester during normal pregnancy and in the presence of culturable microorganisms in the amniotic cavity. These findings provide insight into the soluble host defense mechanisms against intra‐amniotic infection. Abstract : Amniotic fluid concentrations of human beta defensin‐1 (HBD‐1) in women with spontaneous preterm labor and intact membranes. Red lines indicate medians with interquartile ranges.